2022
DOI: 10.1038/s41598-022-13248-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ADS024, a newly characterized strain of Bacillus velezensis with direct Clostridiodes difficile killing and toxin degradation bio-activities

Abstract: Clostridioides difficile infection (CDI) remains a significant health threat worldwide. C. difficile is an opportunistic, toxigenic pathogen that takes advantage of a disrupted gut microbiome to grow and produce signs and symptoms ranging from diarrhea to pseudomembranous colitis. Antibiotics used to treat C. difficile infection are usually broad spectrum and can further disrupt the commensal gut microbiota, leaving patients susceptible to recurrent C. difficile infection. There is a growing need for therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Some operational group B. amyloliquefaciens strains produce proteases ( Cho et al, 2003 ; Devaraj et al, 2018 ). ADS024 also possesses toxin-degrading activities ( O’Donnell et al, 2022 ). Therefore, we attempted to characterize the toxin-degrading effects of ADS024 filtrates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some operational group B. amyloliquefaciens strains produce proteases ( Cho et al, 2003 ; Devaraj et al, 2018 ). ADS024 also possesses toxin-degrading activities ( O’Donnell et al, 2022 ). Therefore, we attempted to characterize the toxin-degrading effects of ADS024 filtrates.…”
Section: Resultsmentioning
confidence: 99%
“…As described previously, isopropanol (IPA) extracts were prepared from the centrifuged bacterial cells ( O’Donnell et al, 2022 ). IPA extracts are enriched in membrane-bound and internal bacterial metabolites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A very promising paper was recently published, in which ADS024, a newly characterized strain of Bacillus velezensis , was identified that appears to have strong activity against C. difficile with negligible impact on the rest of the bacterial flora, and also having protease activity directed against TcdA and TcdB toxins which we have seen to be responsible for the clinical manifestations of this disease [ 73 ].…”
Section: New Therapeutic Strategiesmentioning
confidence: 99%